Specificity of mRNA binding to proteins within the NMD machinery is influenced in cancer - Kalathiya, Umesh; Padariya, Monikaben (Frontiers in Molecular Biosciences, 2025)
IntroductionThe nonsense-mediated mRNA decay (NMD) process is recognized as the quality control of mRNAs to maintain their integrity and production of functional proteins. Readthrough of aberrant mRNA containing premature termination codons (PTCs) can induce the production of truncated proteins with negative functionalities.MethodsTo elucidate the structural and mechanistic basis of NMD components, we performed molecular dynamic simulations (MDS) to analyze their dynamic behavior across different stages of the process. We further investigated how cancer-associated mutations alter mRNA-binding protein (RBP) interactions within the NMD machinery.Results and DiscussionOver the simulation time, the mRNA containing PTCs underwent significant conformational rearrangements, ultimately forming stable interactions with the eukaryotic class-I release factor (eRF1). The efficiency of eRF1 in recognizing stop codons (UAG, UGA, or UAA) nitrogenous bases was identified, revealing a stronger preference toward UAA. Due to the lower structural stability, the AU-rich mRNA motifs showed a diminished eRF1 binding affinity relative to other PTC-containing transcripts. Among the studied cancer variants, the D9Y, R10S, F56V, P89L, and I62M residues were found to either enhance or disrupt eRF1–mRNA interactions. Similarly, when evaluating EIF4A3 RBP from the exon junction complex (EJC), the P114L and G309A mutations significantly impaired the protein–mRNA binding affinity. Surface residue mapping of SMG1 kinase revealed that it engages with SMG8, SMG9, and UPF1 in a sequential binding order, displaying the highest affinity for SMG8. Overall, these findings contribute to the mechanistic understanding of molecular properties for different RBPs from the NMD process, which can be the basis of developing new therapeutic strategies against genetic disease or cancer.